The Improvement of Education Quality - Yossita Wisman; M. Yahya Miskat A.; Putu Sugiantiningsih (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Educational management in strategic, managerial, and operational level determines the quality of education. One important aspect of education management is the issue of educational leadership. Educational leadership, educator standards and education personnel are directly proportional to the quality of education. In other words, the quality of good education is determined by the good leadership of education, well educational leadership will be decisive for the realization of educator standards and education personnel. Effective educational leadership is predicted to be able to support the efforts to realize the standards of educators and educational personnel, which then certainly will also support the efforts to improve the quality of education.The commitment of the parties who involved in educational leadership in order to realize the standards of educators and educational personnel into a necessity.